Drying kinetics in foam layer of mango flesh cv. Haden - Dantas da Silva Filho, Edmilson; Feitosa de Figueirêdo, Rossana Maria; de Melo Queiroz, Alexandre José; Guimarães, Mary Karlla Araújo (Comunicata Scientiae, 2016)
Foam mat drying is an economical process based on the formation of a stable foam by beating the raw material with foam promoters, obtaining after drying a product in a powder form. Thus, the present study aimed to evaluate the drying kinetics of mango flesh cv. Haden with the foam mat drying method at drying temperatures of 50, 60 and 70 ° C, with three different thickness of the layer (0.5, 1.0 and 1.5 cm). The mathematical models of Henderson & Pabis, Henderson and Logarithmic were fitted to experimental data and were used as criteria for evaluating the models the coefficient of determination (R2) and the root mean square deviation (DQM). It was observed that smaller thickness of the foam mat and higher air temperature decreased the drying time. Short drying time occurred at 70 ° C, with 480, 660 and 780 minutes for the thickness of 0.5; 1.0 and 1.5 cm, respectively. The Henderson & Pabis, Henderson and Logarithmic models can be used to represent the drying process since high coefficients of determination (R2) and lower root mean square deviation (DQM) were observed.